2003
DOI: 10.1088/0957-0233/14/6/326
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fibre Bragg gratings and influences on high-power Raman fibre lasers

Abstract: In this paper, some characteristics of fibre Bragg gratings (FBGs) written in Raman fibres, such as insertion losses and spectra, are described. Their influences on a typical Raman fibre laser are numerically simulated. The insufficient FBG bandwidth and depth of a weak FBG will cause a significant leakage of the cavity power. Meanwhile, a large insertion loss of a strong FBG will result in a significant cavity loss. Based on this trade-off, the selection of FBG parameters for this kind of Raman fibre laser is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…5, after 500 round trips). Figures 6 and 7 demonstrate that in the case of more narrow gratings, the ratio between generated power and pump power is lower compared to the case of broader gratings, in agreement with the observations in [15]. We would like to stress once more that the observed behavior should be understood in terms of turbulent-like kinetic mechanisms related to optical wave de-phasing and randomisation, rather than in terms of dynamical interpretation of wave interactions.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…5, after 500 round trips). Figures 6 and 7 demonstrate that in the case of more narrow gratings, the ratio between generated power and pump power is lower compared to the case of broader gratings, in agreement with the observations in [15]. We would like to stress once more that the observed behavior should be understood in terms of turbulent-like kinetic mechanisms related to optical wave de-phasing and randomisation, rather than in terms of dynamical interpretation of wave interactions.…”
Section: Resultssupporting
confidence: 82%
“…However, at high powers, due to nonlinear FWM interactions of the cavity modes, the radiation spectra broaden beyond the grating bandwidth leading to the power leakage out of the cavity and to degradation of the laser performance. It has been already understood that the effect of power overflow due to spectral broadening can be phenomenologically described as a decrease of the mean reflectivity of the FBG mirrors [13][14][15]. In [13] it was pointed out that the standard average power models used to describe Raman fibre lasers have to be modified to account for the effective power-dependent changes of the FBG reflectivity due to spectral broadening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the BVP (2)-(7) with no SpRS (q s = 0, such as used in Ref. [23]) has typically an infinite number of solutions which is not physically meaningful.…”
Section: And 2 Then It Follows Thatmentioning
confidence: 99%
“…Finally, it has been shown that line broadening can significantly stabilize multi-wavelength Raman fiber lasers [16]. The line broadening is usually attributed to nonlinear effects such as four-wave mixing (FWM) or Brillouin scattering [12][13][14]17,18] and there have been several attempts at theoretically calculating the output spectrum of RFLs using various approximations [19][20][21][22][23]. However, a rigorous theoretical treatment of the spectrum of a linear-cavity RFL taking into account FWM without questionable unphysical assumptions has not yet been published.…”
Section: Introductionmentioning
confidence: 99%